2012
DOI: 10.1021/la3013624
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of ZnxCd1–xS@ZnO Core–Shell Nanorods with Enhanced Photocatalytic Activity

Abstract: We report the synthesis of Zn(x)Cd(1-x)S@ZnO nanorod arrays via a facile two-step process and the implementation of these core-shell nanorods as an environmental friendly and recyclable photocatalyst for methyl orange degradation. The band gap of Zn(x)Cd(1-x)S@ZnO core-shell nanorods can be readily tunable by adjusting the ratio of Zn/Cd during the synthesis. These Zn(x)Cd(1-x)S@ZnO core-shell nanorods exhibit a high photocatalytic activity and good stability in the degradation of the methyl orange. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 45 publications
2
45
1
Order By: Relevance
“…6d, which can be deconvoluted into two couple of peaks. Two obvious peaks located at 404.3 and 411.7 eV are observed, which are consistent with the values reported for Cd 2+ [18,19]. This result reveals that Cd element exists in the forms of Cd 3d3/2 and Cd 3d5/2 in the Cd doped MgO sample.…”
Section: Xps Analysissupporting
confidence: 90%
“…6d, which can be deconvoluted into two couple of peaks. Two obvious peaks located at 404.3 and 411.7 eV are observed, which are consistent with the values reported for Cd 2+ [18,19]. This result reveals that Cd element exists in the forms of Cd 3d3/2 and Cd 3d5/2 in the Cd doped MgO sample.…”
Section: Xps Analysissupporting
confidence: 90%
“…To date, many strategies have been developed to enhance the OER activity. One of main routes is to couple photoanode with OER catalysts, such as Pt, RuO 2 , IrO 2 , FeOOH and Ni(OH) 2 [16,21e24]. For example, Shao et al reported ZnO@LDH coreeshell structure for enhanced PEC water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…3 Importantly, the type II core/shell heterostructure nanowires array possesses four advantages: (1) the type II core/shell heterojunctions formed in the interfacial area of the core/shell heterostructures profoundly improve the separation efficiency of photogenerated electron−hole pairs, 4 (2) the large interfacial area of the core/ shell heterostructure warrants fast charge separation and thus enhances the charge-collection efficiency, 5 (3) the shell of the heterostructure not only blocks nonradiative recombination of the electrons in ZnO cores with electrolyte but also provides protection of the ZnO cores from electrolyte-mediated corrosion, 6 and (4) the special topology of the 1D nanostructure array offers a direct electric pathway for the rapid transport of photogenerated carriers to a conductive substrate. 7,8 As a result, much effort has been devoted to fabricating ZnO-based type II core/shell architecture nanowires arrays as photoelectrodes, including heterostructures with a binary shell, such as ZnO/CdS, 2 ZnO/CdTe, 9 ZnO/ZnSe, 10 and ZnO/ In 2 S 3 , 11 and with a ternary shell, such as ZnO/ZnS x Se 1−x 12 and ZnO/Zn x Cd 1−x S. 13 In comparison to heterostructures with a binary shell, ZnObased core/shell heterostructures with a ternary shell are more attractive because of their adjustable composition and band gap, which make the design of the desired photoelectrodes possible. Several synthesis techniques have been exploited to manufacture ternary shells.…”
Section: ■ Introductionmentioning
confidence: 99%